97 A novel missense mutation in SGSH gene causing Sanfillipo type 3A mucopolysaccharidosis. (11th October 2021) - Sansović, Ivona; Odak, Ljubica; Bobinec, Adriana; Barišić, Ingeborg
Abstract : The Sanfilippo syndrome, or mucopolysaccharidosis III, is an autosomal recessive lysosomal storage disease due to impaired degradation of heparan sulphate. A type IIIA (MPS3A; MIM #252900) is caused by homozygous or compound heterozygous mutations in the SGSH gene (MIM #605270) encoding N-sulfoglucosamine sulfohydrolase. MPS IIIA is characterised by progressive central nervous system degeneration manifested as severe intellectual disability (ID)/developmental delay, delayed speech development, autism spectrum disorder and other behavioural problems, epilepsy, and sleep disturbances. Other symptoms include joint stiffness, contractures, scoliosis, hip dysplasia, hearing loss, recurrent respiratory tract and sinopulmonary infections and diarrhoea. Most patients have the onset of clinical symptoms at a mean age of 2.5 years. Clinical features and disease severity vary considerably and the disease course may be rapid or slowly progressive. We report on a seven-year-old boy of a healthy nonconsanguineous family, with clinical features of MPS-III syndrome: macrocephaly, coarse face, thick hair, ID, delayed language and speech development, hyperactivity/attention deficit disorder, elbow stiffness/contractures, mild thoracolumbar scoliosis, lumbar lordosis, mild sensorineural hearing loss, frequent upper-respiratory and ear infections, recurrent loose stools, and abundant excretion of heparan sulphate in the urine. Clinical exome sequencing including GNS, HGSNAT, NAGLU, SGSH genes was performed in family members using Illumina TruSight One Kit. In the SGSH gene, two missense mutations were identified: c.734G>A (p.Arg245His), inherited from the mother, already described and associated with the classic severe phenotype, and a novel, likely pathogenic variant c.1382T>C (p.Leu461Pro) inherited from the father. This sequence change replaces leucine with proline at codon 461 of the protein. Although the function of the domain in which this variant is located is still insufficiently known and the variants in this area are mostly of unknown clinical significance, likely pathogenic computational verdict is based on 10 pathogenic in silico predictions and the classical clinical presentation of this patient. The novel missense mutation reported here, further contributes to the knowledge of the molecular basis of MPSIIIA. As gene therapy is on the horizon, early diagnosis and genotyping are of particular importance for timely targeted treatment. Acknowledgment: This work was supported by Scientific Center of Excellence for Reproductive and Regenerative Medicine and by the EU through the European Regional Development Fund, under grant agreement No. KK.01.1.1.01.0008, project „Reproductive and Regenerative Medicine – Exploring New Platforms and Potentials'.